2006
DOI: 10.1089/scd.2006.15.595
|View full text |Cite
|
Sign up to set email alerts
|

Dental Follicle Progenitor Cell Heterogeneity in the Developing Mouse Periodontium

Abstract: As a developmental precursor for diverse periodontal tissues, the dental follicle (DF) harbors great promise for periodontal tissue regeneration. However, development of optimal therapy awaits the answer to a key question that impinges on many issues in development-Do adult progenitor tissues form a homogeneous cell population that differentiates into target tissues when they arrive at the site, or they contain heterogeneous cell populations that are committed to specific fates? To address the homogeneity/hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
98
1
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(110 citation statements)
references
References 39 publications
7
98
1
4
Order By: Relevance
“…The dental follicle is a condensation of ectomesenchymal cells that surrounds the tooth germ in early stages of tooth formation and contains cells that form the three tissues that constitute the periodontium: periodontal ligament, cementum and alveolar bone [54,72] . When the it was supposed that putative MSCs would be present in the periodontal ligament, which was confirmed in 2004 [73] .…”
Section: Dfpcsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dental follicle is a condensation of ectomesenchymal cells that surrounds the tooth germ in early stages of tooth formation and contains cells that form the three tissues that constitute the periodontium: periodontal ligament, cementum and alveolar bone [54,72] . When the it was supposed that putative MSCs would be present in the periodontal ligament, which was confirmed in 2004 [73] .…”
Section: Dfpcsmentioning
confidence: 99%
“…Moreover, it was observed that, although DePDL and PDSLCs have the ability to differentiate into both adipocyte-like and osteoblastlike cells in vitro, DePDL show a higher potential for adipogenic commitment, and PDLSCs have a higher potential for osteogenic commitment [60] . heterogeneity of DPFCs was analyzed, it was observed that, although all cloned cell lines were positive for MSCrelated surface markers (CD105, CD44, CD29) and negative for hematopoietic markers (CD34, CD117), they were different in terms of proliferation and mineralization patterns, indicating that they could be committed to distinct lineages [72] . In order to avoid donor variability, TDSCs from follicle, pulp and papilla were isolated from a single donor tooth and the morphology, proliferation rate, expression of MSC-specific and pluripotency markers, and in vitro differentiation into osteoblasts, adipocytes, chondrocytes and hepatocyte-like cells were compared [65] .…”
Section: Depdlmentioning
confidence: 99%
“…As a consequence, clonal PDL cell lines derived from mice (Saito et al, 2002), swine (Ibi et al, 2007) and humans (Kamata et al, 2004;Fujita et al, 2005;Pi et al, 2007;Mi et al, 2011) have been developed. In addition, clonal cell lines from mouse dental follicle (DF) cells as a source of PDLSCs have also been reported (Saito et al, 2005;Luan et al, 2006). However, the multipotency in these cell lines has not been analyzed in detail.…”
Section: Pdl Stem Cell Linesmentioning
confidence: 99%
“…In recent years, progenitor cells have been identified in the DF 2,3) , demonstrated to differentiate along osteogenic pathways 4,5) . Additionally, the DF attached to impacted tooth has been used to analyze the differentiation into various cell types including cementoblasts, adipocytes, chondrocytes, fibroblasts or osteoblasts.…”
Section: Introductionmentioning
confidence: 99%